Strengthening the Concept and Self-Image of Junior High School Adolescents as an Effort to Prevent Early Marriage in Kemuning Lor Village, Jember Regency. - Puspitasari, Muthia; Rif"ah, Erwin Nur; Azzahrah, Fatimah; Molasy, Honest Dody (ABDIMAYUDA: Indonesian Journal of Community Empowerment for Health, 2024)
Abstract. Jember Regency is the first region in East Java with the highest rate of child marriage cases. The low self-concept and self-image of adolescents, along with a lack of knowledge regarding reproductive health and the dangers of early marriage, are contributing factors to the prevalence of child marriage cases in Kemuning Lor Village, Arjasa District. Therefore, efforts need to be made to enhance knowledge and awareness through education. This activity employs andragogical methods with an active participative approach through the stages of situation analysis, activity identification and design, participant recruitment, implementation, and activity evaluation. The results of this activity indicate a significant increase in participants' knowledge, as evidenced by the comparison of pre-test and post-test scores. With the implementation of this activity, it is hoped that it will enhance the awareness and motivation of the youth, enabling them to change their mindset in determining the future they desire. Keywords: Child Marriage, Adolescent Self-Image, Reproductive Health, Andragogy, Active Participation Abstrak. Kabupaten Jember merupakan wilayah pertama di Jawa Timur dengan angka kasus pernikahan anak tertinggi. Rendahnya konsep dan citra diri remaja serta rendahnya pengetahuan terkait kesehatan reproduksi dan bahaya pernikahan dini menjadi faktor pendukung maraknya kasus pernikahan anak di Desa Kemuning Lor, kecamatan Arjasa. Oleh karena itu perlu dilakukan upaya untuk meningkatkan pengetahuan dan kesadaran melalui edukasi. Kegiatan ini menggunakan metode andragogi dengan pendekatan active participative melalui tahapan Analisis Situasi, Identifikasi dan Perancangan Kegiatan, Perekrutan Peserta, Implementasi dan Evaluasi Kegiatan. Kegiatan ini didapatkan hasil bahwa terjadi peningkatan pengetahuan peserta yang cukup signifikan dilihat dari perbandingan hasil pengerjaan soal pre test dan post test. Dengan terlaksananya kegiatan ini diharapkan mampu meningkatkan kesadaran dan motivasi para remaja sehingga mampu merubah pola pikir mereka dalam menentukan masa depan yang diinginkan. Kata Kunci: Pernikahan Anak, Citra Diri Remaja, Kesehatan Reproduksi, Andragogi, Active Participative